Facilitated transport of olefin through solid PAAm and PAAm-graft composite membranes with silver ions - Park, YS; Won, J; Kang, YS (ELSEVIER SCIENCE BV, 2001)
Solid poly(acrylamide) (PAAm) composite membranes containing silver ions have been investigated for olefin/paraffin separation. The propylene permeance increased significantly for a solid PAAm/AgBF4 composite membrane with increasing loading amount of silver ions. Silver ions in solid PAAm form reversible complexes with propylene, resulting in the facilitated transport of propylene. The propylene selectivity of 100 over propane was obtained when the mole ratio of silver ions to acrylamide unit was 1. This high separation performance would be obtained predominantly because of the high loading of the propylene carrier, silver ions. PAAm-graft/AgBF4 composite membranes were prepared in order to improve the gas permeance. Introduction of PAAm grafts on a polysulfone microporous membrane surface was confirmed by FT-IR spectroscopy. The propylene permeance was increased through the PAAm-graft/AgBF4 membranes compared to that through of the PAAm/AgBF4 composite membranes, indicating the formation of ultra-thin top layer. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: POLYMER; SEPARATION; COORDINATION; COMPLEXES; NITRATE; BRUSHES